OPTIMIZING THE MANAGEMENT OF STATE-CONFISCATED GOODS IN THE CLASS II TERNATE STORAGE HOUSE OF STATE-CONFISCATED GOODS - Aslan Hasan; Mayadiar A. Redjeb; Ainurrafiqa Pelupessy; Arief Budiono (RADJA PUBLIKA, 2026)
The State Confiscated Goods Storage House (RUPBASAN) holds a strategic position in the criminal justice system as the institution responsible for managing confiscated and seized assets used as evidence in criminal proceedings. Effective asset management is essential to ensure legal certainty, accountability, and the integrity of judicial processes. This study aims to examine the optimization of confiscated and seized asset management at the Class II RUPBASAN in Ternate and to analyze the factors affecting the non-execution of such assets. This research adopts an empirical legal approach, utilizing both primary and secondary data. Primary data were obtained through field interviews, while secondary data consisted of primary, secondary, and tertiary legal materials collected through a literature review. The findings reveal that asset management at the Ternate Class II RUPBASAN—covering receipt, registration, classification, placement, security, maintenance, transfer, disposal, and release—generally complies with applicable regulations. However, shortcomings persist at the receipt stage, particularly in the processes of assessment and examination, due to the absence of qualified personnel. Optimization is therefore required, especially in the stages of receipt, maintenance, and transfer. The study identifies legal factors and law enforcement capacity as the main obstacles to the effective execution of confiscated and seized assets.